Hotspot relaxation time of NbN superconducting nanowire single-photon detectors on various substrates - Zhang, Lu (Sci Rep, 2018)
Hotspot relaxation time (τ(th)) is one of the essential parameter which defines the maximum count rate of superconducting nanowire single-photon detectors (SNSPDs). We studied the τ(th) for NbN-based SNSPDs on various substrates using the two-photon detection method based on the pump-probe spectroscopy technique. We observed that τ(th) strongly increased with increasing bias current in the two-photon detection regime. In addition, the minimum hotspot relaxation time (τ(th))(min) was not significantly affected by the bath temperature; this is different from the previous observations reported for WSi SNSPDs. In addition, a strong dependency of (τ(th))(min) on the substrate was found. The minimum (τ(th))(min) was 11.6 ps for SNSPDs made of 5.5-nm-thick NbN on MgO (100), whereas the maximum (τ(th))(min) was 34.5 ps for SNSPDs made of 7.5-nm-thick NbN on Si (100). We presented a direct correlation between the values of τ(th) and degrees of disorder of NbN films grown on different substrates.